INTERFERENSI FONETIS BAHASA ARAB DALAM BAHASA INDONESIA: ANALISIS UJARAN BAHASA INDONESIA OLEH PENUTUR ARAB - Nasaruddin, Nasaruddin (Sunan Kalijaga State Islamic University Yogyakarta, 2017)
This article aims to analyze the forms of phonetic interference of Arabic language in the Indonesian language speech spoken by an Arabic native speaker. The source of the data and the object of analysis in this article are the recordings of religious lectures of a preacher from Madinah, Saudi Arabia, Sheikh Ali Jabir, which have been delivered in Indonesian language and widely circulated on YouTube site. The lecture recordings are positioned as Indonesian speech events delivered by an Arabic native speaker. The analytical frameworks used in this paper are the theory of the first language interference over the second language, the theory of contrastive analysis, and the theory of error analysis. The interference theory is applied to understand the flow and the form of interference between Arabic and Indonesian language. The contrastive analysis is applied to identify the phonemic differences between Arabic and the Language of Indonesia and to predict the interferences they cause. Meanwhile, the error analysis is applied to identify the forms of phonetic interference of Arabic over the Indonesian language and to explain their causes and motives. This research finds that there are forms of interference of Arabic sounds in Indonesian speeches spoken by an Arabic native speaker which can generally be patterned in two forms, namely, changes in the pronunciation of unknown Indonesian sounds in Arabic, and changes in the pronunciation of the sounds of the Indonesian words derived from the Arabic language. Both of these two patterns are marked by the change of point and manner of articulation of some Indonesian sounds.